2007
DOI: 10.1038/sj.mp.4001940
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic receptor gene variants and risk for autism in the AGRE cohort

Abstract: The b 2 -adrenergic receptor is part of the catecholamine system, and variants at two polymorphic sites in the gene coding for the receptor (ADRB2) confer increased activity. Overstimulation of this receptor may alter brain development, and has been linked to autism in non-identical twins. The objective of this study was to determine whether alleles in ADRB2 are associated with diagnosis of autism in the Autism Genetic Resource Exchange (AGRE) population. Three hundred and thirty-one independent autism case-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…Studies have shown that 5-HT 4 -Rs and ␤ 2 -ARs may play important roles in the neurobiology of depressive disorders [Mongeau et al, 1997;Sastre et al, 2001;Duman, 2007;Lucas et al, 2007;Tamburella et al, 2009], Alzheimer's disease [Lezoualc'h, 2007;Yu et al, 2008Yu et al, , 2010, and autism spectrum disorders [Connors et al, 2005;Cheslack-Postava et al, 2007;Janušonis, 2008;Vincent et al, 2009;Slaten et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 5-HT 4 -Rs and ␤ 2 -ARs may play important roles in the neurobiology of depressive disorders [Mongeau et al, 1997;Sastre et al, 2001;Duman, 2007;Lucas et al, 2007;Tamburella et al, 2009], Alzheimer's disease [Lezoualc'h, 2007;Yu et al, 2008Yu et al, , 2010, and autism spectrum disorders [Connors et al, 2005;Cheslack-Postava et al, 2007;Janušonis, 2008;Vincent et al, 2009;Slaten et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Since 5-HT 4 -Rs receptors may interact with ␤ 2 -ARs during embryonic and fetal development and ␤ 2 -ARs can detect stress-related signals, the ontogeny of 5-HT 4 -R and ␤ 2 -AR levels in the developing forebrain has potentially important implications for understanding autism spectrum and other developmental disorders [Cheslack-Postava et al, 2007;Vincent et al, 2009;Yirmiya and Charman, 2010]. In the present study, we used quantitative reverse-transcription polymerase chain reaction (qRT-PCR) to measure the expression levels of all 5-HT 4 -R splice variants and ␤ 2 -AR in the embryonic mouse telencephalon from embryonic day 13 to birth.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, prenatal environmental exposures and gene-environment interactions involving maternal genes, such as those contributing to regulation of the intrauterine environment or detoxification of exogenous exposures during gestation, could be of prime etiologic significance. The exploration of these direct maternal genetic effects has already begun in some candidate gene studies on the basis of case-parent trio data (24), although optimal designs to test these hypotheses involve the collection of additional genotypic data on grandparents (110). Furthermore, studies of endogenous biomarkers such as the neurotrophic, immune, and endocrine factors, in utero, at birth, and very early in life could also offer clues about dysregulated processes that might, in turn, lead to investigations of candidate genes or specific exposures known to influence these pathways.…”
Section: Future Directionsmentioning
confidence: 99%
“…7 Between commonly shared genes, the most biologicaly plausible are those that are pleiotropic, including b2-adrenergic receptor (ADRB2), vitamin D receptor gene (VDR), leptin (LEP), protein kinase C alpha (PRKCA), and tumor necrosis factor a (TNFa). [8][9][10][11][12] Polymorphisms within ADRB2 were described in association with different disorders, including not only asthma and obesity but also hypertension, 13 autism, 14 cerebral palsy, 15 susceptibility to parasite infestation, 16 and rheumatoid arthritis. 17 The ADRB2 Gene…”
mentioning
confidence: 99%